Comparative Legal Frameworks for the Protection of Child Workers in the Entertainment Industry in Indonesia and the United States - Rahmawati, Sinta; Gunawan Hadi Purwanto (Justitia Jurnal Hukum, 2026)
Legal protection for child performers in the entertainment industry constitutes a complex legal issue due to the tension between economic interests, the rapid growth of conventional and digital entertainment industries, and the fulfillment of children’s rights to education and welfare. This study aims to examine the legal frameworks governing the protection and education of child workers in the entertainment industry in Indonesia and the United States and to formulate an ideal policy framework for Indonesia. The research employs a normative-comparative legal research method. The findings reveal that the United States has established a more comprehensive and structured protection system through a combination of federal regulations, labor union policies, and state-level laws that specifically regulate working hours, mandatory education, working conditions, and the management of children’s earnings. These regulations prioritize the best interests of the child within the entertainment industry. In contrast, Indonesia relies primarily on general labor and child protection laws that do not specifically address the unique characteristics of the entertainment industry, particularly in the digital sector. The absence of specialized regulation creates legal gaps that may lead to violations of children’s rights, including exploitation and disruption of education. Therefore, this study highlights the urgency for Indonesia to develop specific regulations on child workers in the entertainment industry by adopting best practices from the United States while aligning them with national legal principles and child protection norms.